Physical activity and self-esteem: 'Jonny's story'. Issue 5 (2nd September 2016) - Howells, Kristy; Bowen, Jo
ABSTRACT: Previous research has proposed that physical exercise can raise self-esteem. This paper will examine the extent to which physical activity interventions, within one case study primary school supported the development of self-esteem of a (junior) year 5 child over a period of five months. Jonny was 10 years old when the physical activity intervention commenced. His name is a pseudonym to protect his confidentiality. Jonny had been measured on the school's wellbeing measurement scale and was reported to have a very low self-esteem, which had affected his learning through the previous two years in primary school. He was working in the low ability sets for both Mathematics and English and his self-esteem had hindered his ability to make and develop relationships with both adults and peers within his year group. Through participating in the physical activity interventions, Jonny increased the distance that he was able to throw a shot put and hammer, he was able to describe positively his own body movements and he improved his academic performances. The findings suggest that it is possible within a primary school case study setting, to improve self-esteem through physical activity interventions.